From the abstract to the concrete and beyond: : The winding road of constructing a conceptual framework - Vetoshkina, Liubov; Paavola , Sami (Outlines. Critical Practice Studies, 2021)
Methodological procedures are frequently described using ideal-typical sequences and relatively linear phases, often covering the whole research process. We aim to uncover the long-term process of construction of a conceptual framework of a study as constituted by cycles using the method of ascending from the abstract to the concrete (AAC) as a starting point. Empirical research often requires the introduction of intermediate concepts between general theory and data. In this paper we follow how a specific intermediate concept – the intermediary object – was constructed and interpreted in two research cases: 1. the use of building information modelling (BIM) in collaboration between designers, architects and engineers in construction projects; 2. the craft of historical wooden boat building in Russia and Finland. Using ‘manuscript archaeology’ we follow the construction of a conceptual framework by analysing the development of the key texts and documents in these cases. In both cases the process contained multiple ‘episodes’– relatively independent and complete parts of research process, constructed around specific tangible products (like a conference paper or a draft of an article), but forming a sequence when taken together. Each episode contained own cycle of movement from the abstract to the concrete, and the whole research process constituted a relatively autonomous but interconnected network of methodological cycles, where concepts emerged based on conceptualizations from previous episodes. This shows how transmethodological processes of constructing a conceptual framework for a specific study through multiple methodological cycles often develop across a long period, with both vertical movements between theory and data, and horizontal movements between theoretical conceptualizations.